ISLAMIC EDUCATION AS A SOCIAL MOVEMENT: Theoretical Analysis of Ideological Production and the Transformation of Muslim Society - Murdianto Murdianto (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
This article examines Islamic education as a social movement that contributes to ideological production, the formation of habitus, and the transformation of Muslim society in Indonesia. Employing a qualitative methodology, the study utilizes library research to review theoretical works and academic literature on social movements, hegemony, habitus, and the sociology of Islamic education. The findings indicate that Islamic education functions not only as an institution for transmitting religious knowledge but also as a cultural arena where religious values are produced, negotiated, legitimised, and internalised through curriculum, teacher and kiai authority, and everyday social practices. These processes shape a religious habitus that influences religious understanding, social identity, interactional patterns, and collective moral orientation. The theoretical synthesis presented in this article posits that Islamic education is a dynamic socio-cultural movement capable of both reproducing and transforming social structures. The article advocates for strengthening reflective, inclusive, and contextual Islamic education to address global change, the digitalisation of religious authority, and the plural realities of contemporary Muslim society. The implications of this study inform the development of the sociology of Islamic education and the formulation of moderate institutional policy.